2006
DOI: 10.1631/jzus.2006.b0324
|View full text |Cite
|
Sign up to set email alerts
|

Intramammary expression and therapeutic effect of a human lysozyme-expressing vector for treating bovine mastitis

Abstract: Abstract:To develop a gene therapy strategy for treating bovine mastitis, a new mammary-specific vector containing human lysozyme (hLYZ) cDNA and kanamycin resistance gene was constructed for intramammary expression and clinical studies. After one time acupuncture or intracisternal infusion of healthy cows with 400 µg of the p215C3LYZ vector, over 2.0 µg/ml of rhLYZ could be detected by enzymatic assay for about 3 weeks in the milk samples. Western blotting showed that rhLYZ secreted into milk samples from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…As an alternative approach, a gene therapy strategy for treating bovine mastitis was developed in 2006: a new mammary-specific vector containing hLys, cDNA, and the kanamycin resistance gene for intramammary expression and clinical studies was constructed. The clinical studies showed that the injection of the diseased quarters twice with the p215C3LYZ vector had an overt therapeutic effect on bovine mastitis (in particular, clinical mastitis), including the disappearance of symptoms, a significant improvement in the California mastitis test score, and a reasonably high microbiological cure rate [ 214 ].…”
Section: Applications Of Lysozymementioning
confidence: 99%
“…As an alternative approach, a gene therapy strategy for treating bovine mastitis was developed in 2006: a new mammary-specific vector containing hLys, cDNA, and the kanamycin resistance gene for intramammary expression and clinical studies was constructed. The clinical studies showed that the injection of the diseased quarters twice with the p215C3LYZ vector had an overt therapeutic effect on bovine mastitis (in particular, clinical mastitis), including the disappearance of symptoms, a significant improvement in the California mastitis test score, and a reasonably high microbiological cure rate [ 214 ].…”
Section: Applications Of Lysozymementioning
confidence: 99%
“…Lysostaphin transgenic cattle were also protected from an intramammary S. aureus challenge (Wall et al, 2005). A human lysozyme expressing vector for injection into cattle mammary glands has also been created and reported to reduce mastitis symptoms within days (Sun et al, 2006).…”
Section: G Food Safetymentioning
confidence: 99%
“…Vaccines, chemotherapeutic drugs and antibiotics of various generations are currently used for prevention and treatment of mastitis in cattle [21][22][23].…”
mentioning
confidence: 99%